Teaching in Action: A Model to Understand the Complexity of Teachers’ Decisions in Teaching Mathematics - Dimenäs, Jörgen; Taflin, Eva (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2018)
In this article, we focus on the teaching of mathematics in classrooms. The aim of the present study is to create, describe and test a model for teachers' decisions in action when teaching mathematics. We focused on the classroom as a very complex environment and videotaped three excellent teachers teaching mathematics. An inductive iterative research process was selected to generate theory and conclusions directly rooted in data. The model was tested in different teacher groups, and the categories changed and analyses proceeded. The model relates to Jaworski´s (1992), theory the “teaching triad”. By using the developed model “teaching in action” it is possible to analyze and describe teaching in mathematics classrooms and find examples of teachers’ decisions in action. The model “teaching in action” show the complexity of teachers’ work.